(untitled) (Bangladesh Journal of Urology, 2022)
Background: Bulbar urethral strictures require comprehensive and careful urological management. Augmentation urethroplasty is the preferred treatment method and buccal mucosa has gained widespread popularity as the graft of choice for bulbar urethroplasty. Objective: To compare the outcomes of single versus double BMG urethroplasty in the treatment of bulbar urethral stricture. Methods: This prospective observational study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology, Sher-e-Bangla Nagar, Dhaka from July 2018 to December 2019 over a period of one and half years. In this study, 22 patients had single BMG urethroplasty and 38 patients had double BMG urethroplasty. Qmax, dilation requirement, recurrent stricture and postoperative complications were recorded and compared. SPSS 12 was used for analysis. Categorical data were compared with Chi-square test and numerical data were compared with unpaired t test. Results: Maximum patients were more than 40 years old in both groups. Mean age was 40.77 ± 8.52 years & 38.97 ± 10.07 years in single and double BMG group respectively (p>0.05). Most of the patients were either overweight or obese in both groups (p>0.05). In most of the cases aetiology of structure was unknown in both groups. Length of graft was 4.59 ± 0.65 cm and 4.43 ± 0.51 cm in single and double BMG group respectively. Peroperative Qmax was 8.00 ± 1.54 ml/sec and 7.61 ± 1.73 ml/sec in single and double BMG group respectively. Postoperative Qmax after 1 month and after 3 months was significantly higher in double BMG group than single BMG group (23.87 ± 1.79 ml/sec vs 21.73 ± 2.37 ml/sec and 20.71 ± 3.25 ml/sec vs 14.95 ± 1.29 ml/sec). Percent increment of Qmax after 3 months comparing pre-operative was significantly higher in double BMG urethroplasty group than that of single BMG urethroplasty group. Wound infection was higher in single BMG group than that of double BMG group but difference was not statistically significant (27.3% vs 13.2%; p=0.310). Recurrent of stricture was significantly higher in single BMG urethroplasty group than that of double BMG urethroplasty group (45.5% vs 21.1%; p=0.04 Conclusion Double BMG urethroplasty is better than single BMG urethroplasty in the treatment of bulbar urethral strictures. Bangladesh J. Urol. 2021; 24(1): 82-86